Association of supragingival plaque management with subgingival microbiota is moderated by adjunctive antibiotics in stage III-IV periodontitis patients during periodontal therapy - Saberi Kakhki, Kyana Charlotte Laura; Harks, Inga; Matern, Johannes; Prior, Karola; Eickholz, Peter; Lorenz, Katrin; Kim, Ti-Sun; Kocher, Thomas; Meyle, Jörg; Kaner, Doğan; Jockel-Schneider, Yvonne; Harmsen, Dag; et al. (Journal of oral microbiology, 2025)
This study examines the relationship between supragingival plaque control and subgingival microbiota during periodontal therapy, focusing on microbial clusters associated with plaque levels. Data were drawn from a 26-month multicenter, double-blinded, randomized, placebo-controlled trial. Supragingival plaque was measured using the O’Leary index, and subgingival microbiota were profiled via Illumina 16S rRNA gene sequencing. A novel topic modelling approach using cross-validated Latent Dirichlet Allocation (LDA) identified microbial clusters, and negative binomial mixed models evaluated their association with plaque levels. Supragingival plaque was positively associated with bleeding on probing (BOP) and microbial diversity, but not with dysbiosis. A specific subgingival microbial cluster dominated by Selenomonas and Leptotrichia was linked to elevated plaque levels and increased in abundance following both antibiotic and placebo treatments. The odds ratio for plaque associated with this cluster was 1.20 (95% CI: 1.07-1.35). Stratified analyses showed this association was reduced in the antibiotic group but remained in the placebo group. Ineffective supragingival plaque control correlates with increased BOP and microbial diversity, though not necessarily with dysbiosis. Adjunctive antibiotics may promote a more cariogenic subgingival microbiota by disrupting the association between plaque accumulation and the abundance of acidogenic taxa such as Selenomonas and Leptotrichia.